Rethinking corruption - Mungiu-Pippidi, Alina (Rethinking political science and international studies, 2023)
"Driven by an international agenda, the act of 'rethinking' corruption has already taken place more than once in the past two decades, contributing further to a post-truth about corruption than to anything else. This book makes a clear argument in favor of rethinking corruption across any contingency and offers a forecasting method, alongside the latest generation of analytical, fact-based tools to map, assess and predict corruption risk. Mungiu-Pippidi argues that corruption is a policy problem frequently overriding individual choice, and can only be tackled by strong policy interventions, not by 'nudging' every individual into honesty. Chapters explain that corruption has not decreased despite unprecedented efforts because the international context presently creates far more opportunities for it than constraints: few nations, governments or international organizations have proven able to solve the social dilemma of corruption. Meanwhile, many countries, governments, businesses and politicians profit from a world order where integrity cannot be enforced and perpetuate the current status quo. Rethinking Corruption will be crucial reading for academics and students of political science, sociology and law seeking to understand the theoretical dimensions of corruption. It will also be an enlightening read for policy makers, administrators and practitioners looking to rethink how corruption can manifest."